Factors determining the economic performance of businesses in the accommodation, catering and hospitality sector in the Czech Republic during the COVID-19 pandemic - Kozáková, Petra; Děchtěrenko, Filip; Činčalová, Simona; Lízalová, Lenka (Turyzm/Tourism, 2025)
The article is focused on the economic performance of Czech companies in the accommodation, catering and hospitality sector during the COVID-19 pandemic. The aim is to verify the influence of selected factors on their level and development using data from the Albertina database for the period 2018–2021 was used for the analysis. Return on assets (ROA) was selected as the main performance indicator and the indicators monitored included indebtedness, liquidity, size, age of enterprise and the sub-sector to which the enterprise belonged. The results showed that larger businesses and those operating in the hospitality and catering sub-sector managed the difficult situation caused by the pandemic better than those operating in the accommodation sub-sector. The factors of company size and sector therefore had the greatest influence on the value of the ROA economic performance indicator.